2009
DOI: 10.1159/000210400
|View full text |Cite
|
Sign up to set email alerts
|

Expression of p-Akt in Sensory Neurons and Spinal Cord after Peripheral Nerve Injury

Abstract: Akt has been implicated in pro-survival and anti-apoptotic activities in many cell types, including dorsal root ganglion (DRG) and spinal motor neurons. In this immunohistochemical study we have monitored phosphorylated Akt (p-Akt) levels in adult mouse DRGs and spinal cord following unilateral peripheral sciatic nerve transection (axotomy) or carrageenan-induced inflammation. In control animals around half of the lumbar DRG neuron profiles (NPs), mainly small and medium-sized ones, were p-Akt immunoreactive (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
36
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 79 publications
(74 reference statements)
5
36
2
1
Order By: Relevance
“…Numerous studies have demonstrated activation of AKT in DRG and spinal cord neurons following peripheral nerve injury or inflammation (26,58,59,60,71). In the present study, neither AKT nor pAKT was observed in the suburothelial nerve plexus of control or CYP-treated bladder whole mounts.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…Numerous studies have demonstrated activation of AKT in DRG and spinal cord neurons following peripheral nerve injury or inflammation (26,58,59,60,71). In the present study, neither AKT nor pAKT was observed in the suburothelial nerve plexus of control or CYP-treated bladder whole mounts.…”
Section: Discussioncontrasting
confidence: 78%
“…For example, basal AKT phosphorylation is present in rodent lumbosacral dorsal root ganglia (DRG) (58,59) and superficial laminae of the spinal cord (26,60) and significantly increases following peripheral nerve injury or inflammation (26,58,59,60,71). Additionally, colocalization of pAKT with markers of unmyelinated, pain-transducing C-fibers such as IB4, TrkA, calcitonin gene-related peptide (CGRP), and transient potential vanilloid-1 channel (TRPV1) (58,59,71,74) has been demonstrated. Specific inhibitors of AKT signaling including deguelin, AKT Inhibitor IV, SH-6, or NL-71-101 can attenuate mechanical hyperalgesia resulting from intradermal hindpaw capsaicin injection (59,60) or sciatic nerve ligation (71), suggesting a nociceptive role for AKT signaling in peripheral inflammation or injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…administration of rapamycin in the formalin test [40] . Moreover, the upstream molecules PI3K and Akt are strongly increased in DRG neurons after peripheral injury [42,43] . Inhibition of this signaling prevented pain behaviors, implying that the PI3K-Akt-mTOR cascade is essential for pain behaviors.…”
mentioning
confidence: 98%
“…O aumento da fosforilação de Akt também acontece em GRD após a injeção intradérmica de capsaicina in vivo (SUN et al, 2006) e quando a capsaicina também é aplicada in vitro em GRD (ZHUANG et al, 2004), como também há aumento da fosforilação de Akt em GRD de animais após a injeção intraplantar de carragenina (SHI et al, 2009). …”
Section: Dor Inflamatóriaunclassified